Management of Prepartum Vagino-Cervical Prolapse in a Crossbred Heifer: A Case Report - Hanuman Prasad Yadav; Umesh Kumar; Anad Kumar; Sushma L. Baxla (The Indian Veterinary Journal, 2024)
A case of pre-partum uterine prolapse in a HF crossbred heifer associated with inflamed vagina, cervix and uterus is managed with cervico-hysterotomy per-vaginally and delivered dead foetus of four months and prolapsed mass was reduced, repositioned, and retention by rope truss.